Intake and digestibility of two diets for nine-banded armadillos (Dasypus novemcinctus: Linnaeus, 1758) kept under human care - Pinke Testa, Carolyne Assis Eigenheer [UNESP]; Rosa, Patrícia Sammarco; de Castro, Thiago Ferla Novais; Sartori, Maria Márcia Pereira; Hippólito, Alícia Giolo [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Melchert, Alessandra [UNESP] (Wiley, 2023)
The study aimed to evaluate metabolic parameters, nutrient intake, and absorption of two diets formulated for Dasypus novemcinctus armadillos under human care. Were studied two diets: D1—a diet with dry dog food, ground beef, and boiled chicken egg with shells; D2—a diet with the same ingredients as D1, with added banana and papaya. Both are mixed in water. The parameters analyzed were body weight (BW), weight gain (WG), maintenance energy requirement (MER), Lee index, biometrics, body condition score, glucose, triglycerides, total cholesterol, and cholesterol fractions for eight male armadillos. Dietary intake (DI) and efficiency, nutrient intake, metabolizable energy, and digestibility coefficient for the diets were evaluated in six male armadillos. The diet that included fruits showed higher BW, WG, MER, Lee index, and better glucose metabolism. Both diets promoted increases in WG and Lee Index, as well as improvements in glucose metabolism. The diet without fruit improved the lipid profile of the animals. D2 presented the highest DI, better dietary efficiency, and higher energy intake but also a lower crude fiber intake. However, it showed the best utilization of gross fiber and all other nutrients. In conclusion, the diets constituted an adequate nutritional option for captive armadillos and can be used in malnutrition and pathological processes recovery. Although both diets were adequate, the nonfruit diet was preferable due to the improved lipid profile.
Keywords: body condition score; dietary efficiency; recovery; serum glucose and lipids; Xenarthra